Data analysis in transient electronic spectroscopy – an experimentalist's view. Issue 2 (2nd April 2020) - Beckwith, Joseph S.; Rumble, Christopher A.; Vauthey, Eric
ABSTRACT: Time-resolved electronic spectroscopy has grown into a technique that provides hundreds to thousands of electronic spectra with femtosecond time resolution. This enables complex questions to be interrogated, with an obvious cost that the data are more detailed and thus require accurate modelling to be properly reproduced. Analysis of these data comes in a variety of forms, starting with a variety of assumptions about how the data may be decomposed. Here, four different types of analysis commonly used are discussed: band-shape analysis, global kinetic analysis, lifetime distribution models, and soft-modelling. This review provides a 'user's guide' to these various methods of data analysis, and attempts to elucidate their successes, domains in which they may be useful, and potential pitfalls in their usage.